EM Talk: communication skills training for emergency medicine patients with serious illness. Issue 2 (12th January 2016) - Grudzen, Corita R; Emlet, Lillian L; Kuntz, Joanne; Shreves, Ashley; Zimny, Erin; Gang, Maureen; Schaulis, Monique; Schmidt, Scott; Isaacs, Eric; Arnold, Robert
Abstract : The emergency department visit for a patient with serious illness represents a sentinel event, signalling a change in the illness trajectory. By better understanding patient and family wishes, emergency physicians can reinforce advance care plans and ensure the hospital care provided matches the patient's values. Despite their importance in care at the end of life, emergency physicians have received little training on how to talk to seriously ill patients and their families about goals of care. To expand communication skills training to emergency medicine, we developed a programme to give emergency medicine physicians the ability to empathically deliver serious news and to talk about goals of care. We have built on lessons from prior studies to design an intervention employing the most effective pedagogical techniques, including the use of simulated patients/families, role-playing and small group learning with constructive feedback from master clinicians. Here, we describe our evidence-based communication skills training course EM Talk using simulation, reflective feedback and deliberate practice.